Antioxidant capacities and non-volatile metabolites changes after solid-state fermentation of soybean using oyster mushroom (Pleurotus ostreatus) mycelium - He, Mengxin; Peng, Qing; Xu, Xiaoqing; Shi, Bo; Qiao, Yu (Frontiers in Nutrition, 2024)
Given the abundance of beneficial properties and enzymes secreted by edible oyster mushrooms, their mycelium could serve as a starter for fermented foods to enhance their nutritional and bioactive quality. This study aimed to investigate the effects on the nutritional ingredients, antioxidant activity, and non-volatile metabolites during solid-state fermentation (SSF) of soybeans by Pleurotus ostreatus mycelium. The results indicated that the contents of dietary fiber and starch in fermented soybeans decreased, while the amounts of protein and lipid increased after SSF (P < 0.05). Analysis of the total phenolic content (TPC) and antioxidant activities of the fermented soybeans revealed that the methanolic extracts significantly increased TPC and antioxidant activities against intracellular reactive oxygen species (ROS) in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages, as well as against DPPH and ABTS radicals in vitro. A total 154 differential metabolites were identified after SSF, and a Spearman correlation study revealed a direct relationship between antioxidant activities and certain metabolites including phenolic compounds, oligopeptides, and free fatty acids etc. Among these metabolites, phenolic compounds produced by the shikimic acid pathway were diverse in variety and had the greatest multiple differences. The study discovered that a potential mechanism involving SSF with P. ostreatus mycelium increased the antioxidant activity of soybeans.